Pathological Risk Factors and Outcomes in Women With Stage IB2 Cervical Cancer Treated With Primary Radical Surgery Versus Chemoradiotherapy. Issue 8 (October 2015) - Bradbury, Melissa; Founta, Christina; Taylor, Wendy; Kucukmetin, Ali; Naik, Raj; Ang, Christine
<x xml:space="preserve">Abstract</x> Objective Both radical hysterectomy with pelvic lymphadenectomy and primary chemoradiotherapy have been shown to be effective in the management of women with stage IB2 cervical cancer. This study aims to review the outcomes related to each treatment modality and the effects of pathological risk factors on overall survival (OS) and disease-free survival. Methods We performed a retrospective study of 92 women with stage IB2 cervical cancer who were treated at the Northern Gynecological Oncology Center (Gateshead, United Kingdom) across a 22-year period between January 1991 and July 2013. Women were divided into those undergoing primary surgery and those undergoing primary radiotherapy/chemoradiotherapy. The main outcome measures were OS and progression-free survival (PFS). Pathological risk factors of survival were assessed using multivariate analysis. Results Sixty-seven women (72.8%) underwent primary surgery, and 25 women (27.2%) had primary radiotherapy/chemoradiotherapy. Thirty-one of 67 women (46.3%) required adjuvant radiotherapy/chemoradiotherapy after surgery because of positive lymph nodes in 77.4% of cases. The median follow-up was 57.5 months (range, 3–137 months). Thirty-two women (34.8%) had disease recurrence: 6 women (16.7%) in the group undergoing surgery alone, 15 women (48.4%) in the group requiring adjuvant treatment after surgery, and 11 women (44%) in the group having primary radiotherapy/chemoradiotherapy. Overall survival and PFS were higher for women undergoing surgery alone (91.7% and 83.3%) compared with women requiring adjuvant treatment after surgery (54.8% and 51.4%) and those having primary radiotherapy/chemoradiotherapy (60% and 56%) (P = 0.0004 and P = 0.005, respectively). Lymph node metastasis was a significant pathological risk factor of OS and PFS in multivariate analysis. Conclusions Most women require adjuvant treatment after surgery because of positive lymph nodes. Because survival outcomes for women requiring dual treatment are similar to those for women undergoing primary chemoradiotherapy, nodal assessment before definitive treatment should guide the management of these women and identify a low-risk group that can be treated with surgery alone.